Associations between Cloninger’s temperament and character traits and light preference - Hirakawa, Hirofumi; Terao, Takeshi; Kohno, Kentaro; Sakai, Akari; Kawano, Nobuko (Frontiers in Psychiatry, 2025)
BackgroundIt is unknown whether light preference (brightness or darkness) is associated with Cloninger’s temperament and character traits. This study examined the association between Cloninger’s temperament, character, and light preference in healthy individuals. The aim of the present study was to investigate the hypotheses that self-transcendence but not self-directedness may be associated with brightness preference, whereas harm avoidance may be associated with darkness preference.MethodsData from 130 healthy participants were analyzed in an opt-out study. First, the data distribution of temperament and character scores was investigated by Shapiro-Wilk test. If the distribution was not normal, we used non-parametric test to compare temperament and character scores based on light preference (brightness or darkness), morning light exposure (yes or no), and bedtime mobile phone use (yes or no). Second, binomial logistic regression analyses were performed for each temperament and character scores as dependent variables in which the subjects were divided into two groups using median as a cut-off point (less than median = 0, equal to or more than median = 1), with age, sex, light preference, morning light exposure, and bedtime mobile phone use as independent variables.ResultsSelf-directedness was significantly associated with brightness preference and no bedtime mobile phone use. Our hypotheses were not supported.ConclusionsThe present findings suggest that self-directedness may be associated with brightness preference and no bedtime mobile phone use. Further studies are required to determine the causal relationships.